2010
DOI: 10.1021/jp1060039
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Transversal Relaxation of Nitroxides for Pulsed Electron−Electron Double Resonance Spectroscopy in Phospholipid Membranes

Abstract: Pulsed electron-electron double resonance (PELDOR) spectroscopy is increasingly applied to spin-labeled membrane proteins. However, after reconstitution into liposomes, spin labels often exhibit a much faster transversal relaxation (T(m)) than in detergent micelles, thus limiting application of the method in lipid bilayers. In this study, the main reasons for enhanced transversal relaxation in phospholipid membranes were investigated systematically by use of spin-labeled derivatives of stearic acid and phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 52 publications
(194 reference statements)
1
54
0
Order By: Relevance
“…However, utilizing the same spin-labels in phospholipid vesicle membranes homogeneous distributions have been observed. Thus, there is no indication of specific interactions [15]. Furthermore, if the spin-labels form specific structures with short spin-spin distances, their dipolar coupling will be too large to be excited by the microwave pulses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, utilizing the same spin-labels in phospholipid vesicle membranes homogeneous distributions have been observed. Thus, there is no indication of specific interactions [15]. Furthermore, if the spin-labels form specific structures with short spin-spin distances, their dipolar coupling will be too large to be excited by the microwave pulses.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of spin-clusters in lipid vesicle membranes can also be assumed to be homogeneous. The dimension of this homogeneous distribution varies from two to three depending on the sample concentration [13][14][15]. This corresponds to a stretched exponential decay function describing the background [16].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of instantaneous diffusion was employed to measure local concentrations of free radicals appearing in irradiated solids, [10][11][12] and was observed in different other applications, including studies of spin labels in biological systems, 13,14 transition metal ions in solids, 15 phosphorus donors in silicon. 16,17 The echo decay with increasing τ is induced by also spin relaxation of electrons and nuclei, and it depends on the electron spin concentration (due to relaxation of electron spins).…”
Section: "Instantaneous Diffusion" Mechanism In Ese Decaymentioning
confidence: 99%
“…It has been shown that a high local concentration of peptides or proteins in membranes are detrimental for DEER measurement, as it leads to a strong background decay and considerably shortens the phase memory time, T m . [35] Peptide local concentration can be reduced by decreasing the peptide/lipid ratio. It was shown for C-terminal spin-labeled gramicidin A (a membrane-embedded peptide) that increasing the molar ratio from 1:100 to 1:1000 extended T m approximately fourfold.…”
Section: Deer Measurementsmentioning
confidence: 99%
“…It was shown for C-terminal spin-labeled gramicidin A (a membrane-embedded peptide) that increasing the molar ratio from 1:100 to 1:1000 extended T m approximately fourfold. [35] In addition, by using SUVs rather than LUVs one can further reduce the local concentration by minimizing the number of peptides per vesicle. Accordingly, we chose to carry out the DEER measurements in SUVs rather than LUVs.…”
Section: Deer Measurementsmentioning
confidence: 99%